2017
DOI: 10.1182/blood-2017-04-777680
|View full text |Cite
|
Sign up to set email alerts
|

The atypical receptor CCRL2 is required for CXCR2-dependent neutrophil recruitment and tissue damage

Abstract: CCRL2 is a 7-transmembrane domain receptor that shares structural and functional similarities with the family of atypical chemokine receptors (ACKRs). CCRL2 is upregulated by inflammatory signals and, unlike other ACKRs, it is not a chemoattractant-scavenging receptor, does not activate β-arrestins, and is widely expressed by many leukocyte subsets. Therefore, the biological role of CCRL2 in immunity is still unclear. We report that CCRL2-deficient mice have a defect in neutrophil recruitment and are protected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
96
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 79 publications
(108 citation statements)
references
References 51 publications
5
96
6
1
Order By: Relevance
“…Many authors have shown the impact of chemokine receptor complexes (dimers/oligomers) on chemokine functions (Table ). Hauser et al.…”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 99%
“…Many authors have shown the impact of chemokine receptor complexes (dimers/oligomers) on chemokine functions (Table ). Hauser et al.…”
Section: Chemokine Receptor Dimerization/oligomerization: a Potentialmentioning
confidence: 99%
“…; Del Prete et al. ), and published data implicate each of these cells in one or more of the various pathological sequelae induced by O 3 . For example, the use of gadolinium chloride to suppress macrophage function or nedocromil sodium to stabilize mast cell function significantly reduced the ability of O 3 to increase lung permeability and to cause lung inflammation (Kleeberger et al.…”
Section: Introductionmentioning
confidence: 96%
“…; Del Prete et al. ). Because Ccrl2 influences leukocyte migration in the absence of G protein signaling, Ccrl2 is subclassified as an atypical chemokine receptor within the chemokine receptor family (Bachelerie et al.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations